Legal Protection of Workers In Employment Termination Disputes Without Judicial Review - Notodiguno; Budi Santoso; Sugeng Santoso PN (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines legal uncertainty in the resolution of employment termination disputes resulting from the absence of regulation on the extraordinary legal remedy of judicial review (Peninjauan Kembali) under Law Number 2 of 2004 on the Settlement of Industrial Relations Disputes. The research gap lies in the lack of normative analysis explaining the legal rationale and implications of excluding judicial review, despite its recognition in general civil procedural law and judicial practice. This study offers novelty by conceptualizing the exclusion of judicial review as a deliberate legislative policy to ensure finality and expedited dispute resolution in industrial relations. Employing a normative legal research method with statutory and conceptual approaches, the study finds that positioning cassation as the final and binding legal remedy is intended to provide legal certainty and prevent prolonged disputes. Legal protection for workers is achieved when cassation decisions consistently deliver clear legal reasoning and definitive rulings on the fulfillment of workers’ normative rights. Accordingly, consistent treatment of cassation as the ultimate legal remedy is essential to ensuring legal certainty and effective legal protection in employment termination disputes.